2021
DOI: 10.1002/fsn3.2283
|View full text |Cite
|
Sign up to set email alerts
|

Chain length‐dependent inulin alleviates diet‐induced obesity and metabolic disorders in mice

Abstract: Dietary fiber is regarded to improve host metabolic disorders through modulating gut microbiota. The study was to investigate the effects of inulin with different degree of polymerization (DP) on adiposity, related metabolic syndrome, and the possible mechanisms from the points of gut microbiota and metabolite changes. C57Bl/6J male mice were randomly allocated to normal diet (ND) group, high‐fat diet (HFD) group, two HFD groups with short‐chain inulin (HFD‐S) and medium and long‐chain inulin (HFD‐ML) for 8 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…As mentioned above, inulin produces SCFAs, succinic acid, and lactic acid via gut microbiota [ 3 , 22 , 23 ]. Consistent with previous reports [ 12 ], bacterial fermentation in the intestine increased the content of fecal SCFAs in the inulin group. There was a significant increase in the content of postprandial portal vein plasma succinic acid and SCFAs in the inulin group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As mentioned above, inulin produces SCFAs, succinic acid, and lactic acid via gut microbiota [ 3 , 22 , 23 ]. Consistent with previous reports [ 12 ], bacterial fermentation in the intestine increased the content of fecal SCFAs in the inulin group. There was a significant increase in the content of postprandial portal vein plasma succinic acid and SCFAs in the inulin group.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, it has been shown that inulin supplementation exerts a prebiotic anti-obesity, such as the improvement of obesity, blood glucose level, and lipid metabolism. Previous reports have revealed the effect of inulin supplementation on glucose and lipid metabolism in genetically obese mice [ 11 ], or wild-type mice [ 12 , 13 ] or rats [ 14 ] after induction of dietary obesity. Human studies [ 15 , 16 ] have also shown that inulin intake improves glycolipid metabolism, as it is fermented into SCFAs by gut microbiota in the situation of energy excess due to the high-fat and high-sucrose diet (HFHSD), or in the presence of glucose intolerance or obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental animals as well as humans, inulin supplementation has been shown to improve gut ecosystem and reduce the risk of obesity and other metabolic diseases (Li et al., 2021; Reynolds et al., 2019b; Rodriguez, Neyrinck, et al., 2022). This study explored the effect of intervention time of inulin on HFD‐induced obesity in mice.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, medium- and long-chain inulin is regarded as a potential weight loss substance. 93 Additionally, characterizing the microbial composition of obese patients prior to inulin intervention is highly desirable and has a positive impact on subsequent treatment and disease prevention. 94 Therefore, personalized dietary supplements need to be designed for different obese individuals in order to achieve weight loss and maintain physical health.…”
Section: Health Benefitsmentioning
confidence: 99%